Quechua myths in the chronicles: A conciliatory attempt between conqueror and conquered - Nagy, Silvia (1995)
Since time immemorial, man has had within him the desire to know the world and the laws of its operation. This desire to rerum congnoscere causa has prompted the creation of myths, especially myths about the origin of the world and the origin of man, which, in many cases, are linked. In various cultures, origin myths include the motif of the flood. Originally, the purpose of this article was to be a comparative analysis of the role of the flood in Judeo-Christian culture and that of the Incas.